Active power filter with hysteresis current control loop using rectifier boost technique - Rahimi Baharom; Ihsan Mohd Yassin; Nabil Hidayat (Institute of Advanced Engineering and Science, 2020)
This paper presents the Hysteresis Current Control (HCC) to improve the power quality of power electronic converters. The development of HCC was implemented using Active Power Filter (APF) function based on rectifier boost technique to control the range of upper and lower bands. Through this technique, the supply current waveform followed the shape of the sinusoidal reference signal, thus, the distorted input current waveform becomes sinusoidal and in the same phase with the input voltage. As a result, the THD level and switching losses can be reduced, thus improving the power factor of the power supply system. In order to verify the proposed operation, validation of the proposed HCC was done through MATLAB. Selected simulation results are presented.